Role of CMS of «Joomla» in formation IKT-kompetentnosti of pupils of the senior classes pupils in the course of teaching computer science - V I Tsyganov (RUDN Journal of Informatization in Education, 2013)
In article the role of formation of ICT competence at studying senior classes of school at computer science lessons by means of a control system of «Joomla» content is discussed.